2020
DOI: 10.1111/jcal.12471
|View full text |Cite
|
Sign up to set email alerts
|

Understanding student simultaneous smartphone use in learning settings: A conceptual framework

Abstract: Smartphone use in learning settings is a common behaviour amongst college students. Building on the theory of consumerism, self-efficacy and addictive behaviours, the current study developed a three-component conceptual framework to understand college students' smartphone use in organizational as well as self-directed learning settings. One thousand and thirty-three students in Shenzhen completed an online survey that measured their frequency of using smartphones in learning settings, motivation for using smar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 123 publications
1
6
1
Order By: Relevance
“…It could not provide empirical evidence to support previous findings on the direct effect of EMV on intentions (e.g. Fu et al, 2020;Olufadi, 2015;Watjatrakul, 2020;Watjatrakul and Hu, 2017). The study found three significant factors of perceived values of MLA (FUV, SPV and SOV) that positively affect learners' ICU.…”
Section: Findings and Discussioncontrasting
confidence: 84%
See 2 more Smart Citations
“…It could not provide empirical evidence to support previous findings on the direct effect of EMV on intentions (e.g. Fu et al, 2020;Olufadi, 2015;Watjatrakul, 2020;Watjatrakul and Hu, 2017). The study found three significant factors of perceived values of MLA (FUV, SPV and SOV) that positively affect learners' ICU.…”
Section: Findings and Discussioncontrasting
confidence: 84%
“…Several studies examined perceived values associated with learners' behavioral intentions to adopt in different contexts based on TCV. For example, mobile coupon applications (Liu et al, 2015), online learning adoption (Watjatrakul, 2016), the Internet as a retailing platform (Cheng et al, 2009), the continued use of mobile phones during the lecture (Olufadi, 2015), e-book adoption (Watjatrakul and Hu, 2017) and smartphone use in the organization and selfdirected learning settings (Fu et al, 2020). Other studies examined perceived values based on CVT, particularly ethical and spiritual values.…”
Section: Theoretical Background 21 Perceived Valuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of differences between respondents of different sexes showed that girls are more prone to cyberloafing than boys. Similar data were obtained when studying the use of smartphones by students from China [30].…”
Section: Resultssupporting
confidence: 71%
“…It is well known that m‐learning is a natural evolution of e‐learning caused by the ubiquitous character of mobile devices (Barnes et al, 2019; Zhai & Shi, 2020). The users, who are familiar with, or even addicted (Andrade et al, 2020; Kuem et al, 2020; Tangmunkongvorakul et al, 2020) to mobile gadgets, do not have to change anymore the device when shifting from basic phone‐related activities (calls, messaging, and emails) to personal needs (order food, shopping, booking for various services), entertainment (social media, games, movies, news), but also working or learning (Fu et al, 2020). Moreover, studies like (Buchmann & Karagiannis, 2017) demonstrate that m‐learning is not exclusively designed for schools or universities.…”
Section: Introductionmentioning
confidence: 99%